Unveiling the Impact of the Genomic Architecture on the Evolution of Vertebrate microRNAs - França, Gustavo S.; Hinske, Ludwig C.; Galante, Pedro A. F.; Vibranovski, Maria D. (Frontiers in Genetics, 2017)
Eukaryotic genomes frequently exhibit interdependency between transcriptional units, as evidenced by regions of high gene density. It is well recognized that vertebrate microRNAs (miRNAs) are usually embedded in those regions. Recent work has shown that the genomic context is of utmost importance to determine miRNA expression in time and space, thus affecting their evolutionary fates over long and short terms. Consequently, understanding the inter and intraspecific changes on miRNA genomic architecture may bring novel insights on the basic cellular processes regulated by miRNAs, as well as phenotypic evolution and disease related mechanisms.